2015
DOI: 10.1371/journal.pone.0131678
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Drivers of Academic Success in Surgery: An Analysis of 3,850 Faculty

Abstract: ObjectiveDetermine drivers of academic productivity within U.S. departments of surgery.MethodsEighty academic metrics for 3,850 faculty at the top 50 NIH-funded university- and 5 outstanding hospital-based surgical departments were collected using websites, Scopus, and NIH RePORTER.ResultsMean faculty size was 76. Overall, there were 35.3% assistant, 27.8% associate, and 36.9% full professors. Women comprised 21.8%; 4.9% were MD-PhDs and 6.1% PhDs. By faculty-rank, median publications/citations were: assistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 27 publications
0
32
1
Order By: Relevance
“…3 Valsangkar et al found that the presence of a PhD degree significantly correlated with increased publications and citations for assistant professors ( p < 0.001), associate professors ( p < 0.001), and professors ( p < 0.05). 3 The same study also determined that history of NIH funding significantly correlated with increased academic productivity. 3 Our results also show that the number of NIH grants was significantly associated with h-index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Valsangkar et al found that the presence of a PhD degree significantly correlated with increased publications and citations for assistant professors ( p < 0.001), associate professors ( p < 0.001), and professors ( p < 0.05). 3 The same study also determined that history of NIH funding significantly correlated with increased academic productivity. 3 Our results also show that the number of NIH grants was significantly associated with h-index.…”
Section: Discussionmentioning
confidence: 99%
“…13 Traditionally, scientific eminence has been quantified by total publication or citation count. However, these cumulative metrics do not sufficiently evaluate the quality of one’s scholarly output.…”
mentioning
confidence: 99%
“…It is well established that the number of publications and citations correlate with academic rank and this has been shown in multiple specialties including General Surgery, Neurosurgery, Otolaryngology, Urology, and Anesthesia [10,[21][22][23][24]. Here it is demonstrated that membership in an academic surgical society, the SUS, is also correlated with an increased number of publications and citations.…”
Section: Discussionmentioning
confidence: 61%
“…While not exhaustive, some data do exist on the metrics between different departments within medical schools [9]. The authors of this study have previously demonstrated within academic surgical departments, scholarly productivity is driven by divisions of research, general surgery, and transplant surgery [10].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation